PENGARUH KOMPETENSI DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA DI PT. TRACTORINDO MITRA UTAMA MOJOKERTO - Yusuf Indrajaya (Jurnal Manajerial Bisnis, 2023)
Human resources (HR) are very important assets for the company. The performance of a company will be good if the employees have good competence. Employee competence has an influence on employee performance which is also related to workload factors to complete tasks. In market competition, the company must have an advantage over competing companies. Employee competency development is expected to increase motivation to work productively. High employee motivation will have a positive impact on the company. This type of research is an explanatory study with a quantitative approach. The sample used is all members of the population, namely 55 employees at PT. Tractorindo Mitra Utama. Based on the results of the analysis, it was found that competence had a positive and significant effect on performance (p-value = 0.001), workload had a negative and significant effect on performance (p-value = 0.017), motivation had a positive and significant effect on performance (p-value = 0.015) , Competence has a positive and significant effect on motivation (p-value = 0,000), workload has a negative and significant effect on motivation (p-value = 0,000), competence through work motivation has a positive and significant effect on performance (p-value = 0.013), and Workload through Work Motivation has a negative and significant effect on performance (p-value = 0.014).